2009
DOI: 10.1038/ejcn.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

An inverse relationship between plasma n-3 fatty acids and C-reactive protein in healthy individuals

Abstract: High sensitivity C-reactive protein (hs-CRP) is a marker of low-grade sustained inflammation. Omega-3 (n-3) fatty acids have anti-inflammatory properties and are associated with reduced cardiovascular disease (CVD) risk. The aim of this study was to investigate whether plasma n-3 fatty acid concentration is related to hs-CRP concentration. A total of 124 free-living adults, were divided into tertiles of plasma hs-CRP (o1.0, 1.0-3.0 and 43.0 mg/l). Body composition and anthropometric measurements were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 10 publications
6
65
0
3
Order By: Relevance
“…They reported that PUFAs, and especially total n-3, were independently associated with lower levels of pro-inflammatory markers (CRP, IL-6, IL-1ra, and TNFα) and higher levels of anti-inflammatory markers (soluble IL-6r, IL-10, and TGFβ) independent of confounders. Though a systematic review by Balk et al [47] reported mixed effects of n-3 PUFAs on serum markers of CVD risk, the present study findings are more in agreement with the many studies reporting an inverse relationship between the intake of n-3 and biomarkers of inflammation in healthy subjects and other human trials [48][49][50][51][52]. Collectively, these studies support the significant benefits of increasing low n-3 PUFA levels to help balance the n-6:n-3 ratio, and our results indicate that it is possible to achieve this goal efficiently with four weeks of n-3 EPA and DHA oral supplements in a young adult sample, and that this was associated with reduced CRP.…”
Section: Discussionsupporting
confidence: 82%
“…They reported that PUFAs, and especially total n-3, were independently associated with lower levels of pro-inflammatory markers (CRP, IL-6, IL-1ra, and TNFα) and higher levels of anti-inflammatory markers (soluble IL-6r, IL-10, and TGFβ) independent of confounders. Though a systematic review by Balk et al [47] reported mixed effects of n-3 PUFAs on serum markers of CVD risk, the present study findings are more in agreement with the many studies reporting an inverse relationship between the intake of n-3 and biomarkers of inflammation in healthy subjects and other human trials [48][49][50][51][52]. Collectively, these studies support the significant benefits of increasing low n-3 PUFA levels to help balance the n-6:n-3 ratio, and our results indicate that it is possible to achieve this goal efficiently with four weeks of n-3 EPA and DHA oral supplements in a young adult sample, and that this was associated with reduced CRP.…”
Section: Discussionsupporting
confidence: 82%
“…5). In contrast, the plasma high-sensitivity CRP and EPA concentrations exhibit a negative correlation 99) . The administration of hp-EPA-E (Epadel ship between EPA and CVD, and the JELIS study recently demonstrated that EPA administration reduces the risk of CVD.…”
Section: Relationship Between the (Pgi2+pgi3)/txa2mentioning
confidence: 88%
“…Поэтому содержание НЭЖК+АЛБ в сыворотке крови, увели-чение содержания СРБ в субклиническом (клиническом) интервале, гипертриглицеридемию, повышение в плазме крови содержания тиреоидных гормонов, гормона роста, глюкокортикоидов и эстрогенов можно рассматривать как маркеры патофизиологичных состояний, которые формируют резистентность к ИНС [45,46]. Если в плазме крови повышено содержание СРБ, это можно рассма-тривать как тест РИ; к тому же, СРБ негативно соотно-сится с содержанием в плазме крови ω-3 ЭС-поли-ЖК [47]. Уровень ХС в ЛП не помогает диагностике РИ [48].…”
Section: вестник рамн /2012/ №unclassified